Creating the system of social partnership as a management mechanism in contemporary enterprises: worldwide experience and Ukrainian peculiarities - Vladimir Lazarenko (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Міжнародні відносини, економіка, країнознавство, туризм, 2019)
Great majority of studies of the social interaction within the system of Ukrainian enterprises management are devoted to the mere description of its forms and mechanisms dominant in the developed market countries, being oriented at their sole imitation within the transitional economy. The subject of the article was to reveal the particularity of formation of the social partnership system at the contemporary enterprises of Ukraine. Principal aim was to delineate the potentialities that these companies possess in utilizing the worldwide experience of the corporate governance. Main tasks of the study were to: expose the behavioral particularities of varied enterprise governance subjects in the post-command economy; detect the interconnections between models of the management and social dialogue formed at the privatized enterprises; outline the objective limitations and possibilities of reworking the international experience of social partnership and corporate governance to the transitional economy conditions. The factual evidence was drawn from the external and internal data of the Ukrainian corporate bodies and its generalization by the National Commission on SSM at various stages of enterprises operation. The study methodology comprises systemic, factorial and statistical analysis. Main results include: demonstration of vital necessity that the first-hand consideration of the nationally-based forms of all economic actors’ interaction has in constructing the institutes of enterprise governance in Ukraine; elucidation of algorithm of the different social partnership system elements enhancement; and elaboration of forecast of its effects in optimizing the management process at the national and international companies in economy of Ukraine.